Constructing a Public Comparative Theology: Examining Ernst Troeltsch through a Critical Hermeneutic Lens - Chung, Paul (International journal of public theology, 2018)
This article explores Ernst Troeltsch’s potential contribution to a Christian public theology. It does so by way of a case being made for a public comparative theology. For this purpose I reconsider investigating Troeltsch’s sociological method through a critical hermeneutic lens provided by Hans G. Gadamer’s hermeneutics and Jürgen Habermas’ sociology of a lifeworld. Through this hermeneutical mediation I propose a more comprehensive understanding of Troeltsch’s project, and how it can bring relevancy to a public theology that takes into account the comparative study of religions in our pluralist context. Troeltsch’s work will thus be hermeneutically refined in a socially responsible manner in keeping with the reality of multiple modernities and the religious humanism in our contemporary context.